The Relationship of Knowledge and Attitudes of Adolescent Women and the Incident of Early Marriage - Sari, Dewi Puspito; Maharani, Nine Elissa; Suryaningsih, Anisa Dewi (Jurnal Keperawatan Jiwa, 2024)
The early marriage rate in Karanganyar Regency in 2022 is ranked 26th in Central Java and 3rd in Surakarta. Limited knowledge can lead to risky behavior that results in early marriage. The attitude of adolescents is often indifferent in responding to the phenomenon of early marriage. The purpose of this study was to determine the relationship between the knowledge and attitudes of young women and the incidence of early marriage in Karanganyar Regency. This research is a quantitative descriptive correlation with a cross sectional approach. The population of this study were 196 young women in Karanganyar Regency whose early marriage proposals were granted in 2022 with a sample of 96 young women in Karanganyar Regency whose early marriage proposals were granted in 2022. The sampling technique was purposive sampling. Data was taken using a questionnaire through chi square analysis with a confidence level of 95% (α = 5%).  The results of univariate analysis showed that there were 80 young women (83.3 % ) who had low knowledge about the incidence of early marriage. There were 77 young women (80.2 % ) who had a negative attitude towards the incidence of early marriage. The incidence of early marriage was dominated by the very early category of 5 3 young women (5 5.2 %). The results of the chi square test showed that there was a relationship between the knowledge of young women and the incidence of early marriage in Karanganyar Regency with a p-value of 0 , 0 22 <0 , 05 and there was a relationship between the attitudes of young women and the incidence of early marriage in Karanganyar Regency with a p-value of 0 , 0 2 < 0 , 05. It is recommended that young women increase their desire to explore health information and education and be able to take part in activities carried out by health workers for young women regarding early marriage and its impacts.